PEST CONTROL OF CLOVE STEM BORNS (Hexamitodera semivelutina L.) USING PESTICIDES VEGETABLE LEAVES OF GAMAL (Gliricidia sepium) - Manuel Ponomban; James B. Kaligis (Sam Ratulangi University, 2020)
Cloves (Syzigium aromaticum L) are commercial crops in Indonesia with a high economic value. In Indonesia, clove production is concentrated in West Sumatra, North Sulawesi, and Maluku. This commodity is widely used in the industrial sector as an ingredient in the production of kretek cigarettes, as well as in the pharmaceutical sector as an ingredient in the production of essential oils. North Sulawesi, the country's largest clove producer, has made a significant contribution. Pests and diseases are two of the most common obstacles in clove cultivation. Pest and disease attacks have a significant impact on clove crop production. Pest infestations can cause plant growth to be disrupted, production to be reduced and even death of plants.Â This pest attack has been reported to attack clove plants in North Sulawesi since 1966, with the percentage of clove trees attacked by stem borer reaching 43.3 percent and a mortality rate of 14.2 percent. Until now, the most common pest complaint among farmers has been the attack of the stem borer H. semivelutina.Keywords: Â Clove; Borer Pests; Vegetable PesticidesAbstrakCengkih (Syzigium aromaticum L) merupakan tanaman perdagangan yang mempunyai nilai ekonomi cukup tinggi di Indonesia. Sumatera Barat, Sulawesi Utara, dan Maluku merupakan sentra cengkeh di Indonesia. Komoditi ini banyak digunakan di bidang industri sebagai bahan pembuatan rokok kretek, dan dibidang farmasi sebagai bahan pembuatan minyak atsiri. Sulawesi Utara sebagai penghasil utama cengkeh nasional yang memberikan kontribusi besar. Kendala yang sering dijumpai dalam budidaya cengkeh adalah serangan hama dan penyakit. Serangan hama dan penyakit sangat berpengaruh terhadap produksi tanaman cengkeh. Serangan hama dapat mengakibatkan pertumbuhan tanaman terganggu, produksi menurun bahkan kematian tanaman. Di Provinsi Sulawesi Utara, seranngan hama ini sudah dilaporkan menyerang tanaman cengkeh sejak tahun 1966 dimana persentase pohon cengkeh yang terserang penggerek batang ini dilaporkan mencapai 43,3% dengan angka kematian mencapai 14,2 %. Sampai pada saat ini hama yang sering dikeluhkan oleh petani adalah adanya serangan penggerek Batang H. Semivelutina.Kata Kunci: Â Cengkih; Hama Penggerek; Pestisida Nabati